Discovery learning and motor ability effects on students’ discus throw learning outcomes - Fitriyanti Fitriyanti; Eri Barlian; Arsil Arsil; Damrah Damrah (Journal of Educational and Learning Studies, 2026)
This study examined the effects of Discovery Learning and Conventional Learning, as well as their interaction with motor ability, on discus throw learning outcomes among eighth-grade students. A 2 × 2 factorial experimental design was conducted with 40 students from SMP Negeri 1 Pasaman. Participants were classified into high- and low-motor-ability groups and assigned to either Discovery Learning or Conventional Learning. Data were analyzed using descriptive statistics and two-way ANOVA (α = .05). Discovery Learning significantly outperformed Conventional Learning (F = 50.29, p < .001). A significant interaction was found between learning model and motor ability (F = 50.10, p = .048). Students taught through Discovery Learning achieved higher mean scores than those receiving Conventional Learning in both high (13.37 vs. 11.58) and low (12.72 vs. 11.40) motor-ability groups. Discovery Learning is more effective than Conventional Learning for improving discus throw learning outcomes, and its effectiveness is influenced by students’ motor ability